2007
DOI: 10.2165/00002018-200730010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-Associated Myocarditis

Abstract: Clozapine is uncommonly but importantly related to myocarditis, often fatal or near fatal and sometimes in relatively young patients with early onset after treatment initiation. The most striking feature about this condition is the wide diversity of nonspecific symptoms that occur in afflicted patients. Additional pharmacovigilance, improved reporting systems and further investigation of mechanisms of drug-induced myocarditis and related cardiovascular conditions (such as heart failure) are clearly warranted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(70 citation statements)
references
References 32 publications
2
65
0
3
Order By: Relevance
“…As a general rule, clozapine should always be suspected as a potential culprit when a patient develops new or worsened physical symptoms, in particular when the symptoms point to a systemic process and appear in the early stages of treatment. Most cases of myocarditis, pericarditis and lung disease seem to develop within 2 to 3 weeks of commencing clozapine [20]. It should also be taken into account that the concomitant use of psychotropic drugs adds to the risk of developing serious adverse effects, as does comorbid metabolic syndrome, heart and lung disease [21–25].…”
Section: Discussionmentioning
confidence: 99%
“…As a general rule, clozapine should always be suspected as a potential culprit when a patient develops new or worsened physical symptoms, in particular when the symptoms point to a systemic process and appear in the early stages of treatment. Most cases of myocarditis, pericarditis and lung disease seem to develop within 2 to 3 weeks of commencing clozapine [20]. It should also be taken into account that the concomitant use of psychotropic drugs adds to the risk of developing serious adverse effects, as does comorbid metabolic syndrome, heart and lung disease [21–25].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of clozapine induced myocarditis has been estimated to be as high as approximately 1% of patients starting clozapine92 although others have found a lower incidence of about one in five hundred 93. It should be noted that although no definitive increased risk for myocarditis has been identified with other agents, quetiapine has been raised as a possible cause in several reported cases of myocarditis as well 94…”
Section: Myocarditismentioning
confidence: 99%
“…The majority of clozapine-induced myocarditis occurs within the first 4 weeks of treatment, usually between days 14 and 21, although cases have been reported more than a year after treatment initiation 92,95. No specific monitoring guidelines have been recommended in the United States although guidelines have been proposed in Australia including baseline C-reactive protein (CRP), cardiac enzymes, and echocardiography 95…”
Section: Myocarditismentioning
confidence: 99%
“…Another study reported the incidence rate of any clozapine adverse reactions to be 0.7–1.2% among treated patients (4). The psychiatry unit of the hospital in question could accommodate up to 27 psychiatric patients at a given time.…”
Section: Discussionmentioning
confidence: 99%
“…Myocarditis may be related to clozapine dosages between 100 and 450 mg (4). The US FDA Report from the 1990s suggested that the median daily clozapine dose of 450 mg was observed in patients who survived and 400 mg of patients who died from clozapine-induced myocarditis (2).…”
Section: Discussionmentioning
confidence: 99%